Classically Bonded Chalcogenide Anions of Tin, Thallium, and Lead in Basic Media - Pirani, Ayaaz M. (My University, 1997)
This Thesis describes the preparation of classically-bonded chalcogenide anions of tin, thallium, and lead in basic media and their structural characterization in solution by multi-nuclear magnetic resonance (multi-NMR) spectroscopy and in the solid-state by single-crystal X-ray crystallography and vibrational (Raman) spectroscopy. The Sn₂Ch₆⁴⁻ and Sn₂Ch₇⁴⁻ (Ch = Se, Te) anions have been characterized in solution for the first time by multi-NMR spectroscopy. The magnitudes of the relativistically corrected reduced coupling constants ¹K(Sn-Cht)RC, ¹K(Sn-Chmb)RC, and ¹K(Sn-Chdb)RC were shown to be consistent with a significant degree of s-character in the bonding. The Sn-Chmb and Sn-Cht bond distances observed in the X-ray crystal structures of the Sn₂Ch₆⁴⁻ anions were shown to correlate with the ¹K(Sn-Cht)RC values, indicating that the solid-state molecular structures of the anions are retained in solution. The Raman spectra of the Sn₂Ch₆⁴⁻ anions are also reported along with their respective factor-group analyses. The novel HOSnTe₃³⁻ anion, the hydroxide derivative of SnTe₃²⁻, has been structurally characterized by X-ray crystallography and represents the first example of a simple mixed hydroxychalcogenide anion of tin. The novel of Sn₄Ch₁₀⁴⁻(Ch = Se, Te) have been characterized for the first time in solution by ⁷⁷Se, ¹¹⁹Sn, and ¹²⁵Te NMR spectroscopy and in the solid-state by X-ray crystallography and Raman spectroscopy. The solid-state and solution anion geometry is of the adamantanoid type where the Snᴵᵛ atoms occupy the bridgehead position and the Ch atoms occupy the bridging and terminal sites. The Raman spectra of the Sn₄Ch₁₀⁴⁻ anions have been assigned and compared with those of related adamantanoid systems and SnSe₄⁴⁻. The X-ray crystal structure of the novel adamantanoid Sn₄Se₉⁴⁻ anion is also reported and represents the first example of a P₄O₉-type post-transition element anion containing tin and a chalcogen. The solution and X-ray crystal structure of the TI₂Te₂²⁻ anion and the vibrational spectra of the TI₂Ch₂²⁻ (Ch = Se, Te) anions have been determined. Density functional theory calculations at the local and nonlocal levels confirm that the butterfly geometries observed in the solid state are true minima in the gas phase but are highly deformable. This finding is supported by the variation of the ²⁰⁵TI-²⁰³TI spin-spin coupling constants in the TI₂Ch₂²⁻(Se and/or Te) anions with solvent and temperature and by the observed and calculated low vibrational frequencies of the anion inversion modes. Theory indicates that the TI-Ch bonds are essentially pure p in character and a significant concentration of s-electron density along the TI∙∙∙TI axes and is supported by the small magnitudes of ¹K(TI-Ch)RC and the large magnitudes of K(TI-TI)RC observed for the TI₂Ch₂²⁻ (Ch = Se and/or Te) anions in solution. The series of Group 14 metal trigonal bipyramidal M₂Ch₃²⁻ (M= Sn, Pb; Ch = S, Se, and/or Te) anions has been extended to the mixed-metal TIMTe₃³⁻ (M = Sn, Pb) anions which were characterized in solution by ¹¹⁹Sn, ¹²⁵Te, ²⁰⁷Pb, and ²⁰⁵TI NMR spectroscopy. The TIPbTe₃³⁻anion was also characterized by X-ray crystallography in the compound (2,2,2-crypt-K⁺)₃TIPbTe₃³⁻∙2en. The small magnitudes of ¹K(M-Ch)RC observed for M₂Ch₃²⁻ and TIMTe₃³⁻are consistent with predominantly p-bonded cages and is supported by local and nonlocal density functional theory calculations which indicate that the experimental structures are true minima. Although theory indicates weak M∙∙∙M interactions of high s orbital character on M, the large K(M-M)RC and K(TI-M)RC couplings appear to arise predominantly from multiple coupling pathways and can be rationalized in terms of the small M-Ch-M bond angles observed in the X-ray crystal structures. The novel TI₂Seᵪⁿ⁻, TI₃Seᵧᵐ⁻, and TI₃Sezᴾ anions have been obtained by extraction of the alloys NaTISe and NaTI₀.₅Se in en and liquid NH₃ in the presence or absence of 2,2,2-crypt and characterized by variable-temperature ⁷⁷Se, ²⁰³TI, and ²⁰⁵TI NMR spectroscopy. Although the detailed solution structures of the anions have not yet been determined, they were shown by an analysis of the TI-TI spin-spin coupling patterns and the ²⁰³TI and ²⁰⁵TI subspectra arising from natural abundance isotopomer distributions to be di- and trinuclear with respect to thallium. The X-ray crystal structures of the novel TI₄Se₈⁴⁻ and [TISe₄/₂⁻]¹ anions are also reported and represent rare examples of thallium selenide polyanions.
Keywords: Chemistry; Chemistry